NEW DATA ON THE SAFETY OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS: THE CONCEPT OF THE HIGH CLASS-SPECIFIC CARDIOVASCULAR RISK OF SELECTIVE CYCLOOXYGENASE-2 INHIBITORS IS OUTDATED - A. E. Karateev; D. S. Novikova; E. L. Nasonov (Научно-практическая ревматология)
The results of the PRECISION trial were published in late 2016. During this trial, a total of 24,081 patients at high cardiovascular risk took celecoxib 200-400 mg/day, naproxen 750–1000 mg/day or ibuprofen 1800–2400 mg/day for more than 1.5 years (20.3±16.0 months). The findings show that the frequency of vascular catastrophes (death, nonfatal myocardial infarction, and stroke) in patients receiving celecoxib was not higher than that of the similar complications in those taking the control drugs. At the same time, celecoxib demonstrated a statistically significant advantage in reducing the risk of serious gastrointestinal complications. New evidence refutes the concept of high cardiovascular risk that is common to all coxibs and confirms the provisions of national guidelines for the rational use of nonsteroidal anti-inflammatory drugs (NSAIDs), which were published in 2015. This review presents recent data on the risk of NSAID-related complications, including a brief description of the design and results of the PRECISION trial.